The Influence of Multirepresentation Based Science Student Worksheets Integrated with Virtual Laboratory on the Critical Thinking Skills of Junior High School Students - Taqiyya, Bela Zain; Mahardika, I ketut (International Journal of Education, Information Technology, and Others, 2026)
This study aims to examine the effect and increase in the use of multirepresentation-based science worksheets integrated with virtual laboratories on the critical thinking skills of junior high school students. The research method used is a quasi-experiment with a non-equivalent control group design. The research subjects consisted of 54 seventh-grade students at SMP Negeri 14 Jember in the odd semester of the 2025/2026 academic year, who were divided into an experimental class and a control class. Data collection techniques were carried out through pretest and posttest administration, while data analysis included normality tests, independent samples t-tests, and n-gain tests to determine the improvement in students' critical thinking skills. The results showed that the use of multirepresentation-based science worksheets integrated with virtual laboratories had a significant effect on improving students' critical thinking skills.